Factors affecting the supply of glucose to the heart of the rat, in vivo. - Daniel, P M (1980)
1. The influx of glucose into the heart of intact, living, anaesthetized rats was measured when the levels of insulin the blood were (a) low (as a result of fasting), (b) normal, and (c) high (as a result of injecting insulin). The findings showed that the transport of glucose into cardiac cells is carrier-mediated and is strongly insulin-independent. 2. The major barrier to the supply glucose to the heart from the circulating blood is at the surface membrane of the cardiac cells, rather than at the endothelium of the cardiac capillaries. 3. The extracellular space of the heart was measured and was found to be approximately 25% of the cardiac tissue. 4. During life, glucose, as well as its analogue, 3-O-methylglucose passes across the membranes of the cells of the heart by means of a transport system which is strongly dependent upon insulin and appears to be carried-mediated. A likely explanation for the effect of insulin is that it increases considerably the affinity of the transport carrier for glucose. Saturation of the carrier takes place when the levels of insulin and of glucose in the blood are high. However, when the concentration of insulin is low, e.g. during a fast, the affinity of the carrier for glucose is reduced so that saturation cannot be demonstrated. 5. It is suggested that the low level of insulin that is found in the blood in the early morning, which is due to the night fast, may lead to the cardiac dysfunction which often develops at that time.